The Usage of Wetbond-SP and Retona Blend 55 on Hotmix Asphalt - Mangiring Andronikus; Nataadmadja Adelia Dwidarma (E3S Web of Conferences, 2023)
The flexible pavement layers are very susceptible to damage due to moisture or water. Excess moisture on any of pavement layers can cause damage before the designed pavement lifetime. To improve the quality of flexible pavement layers, modifications to asphalt mixtures are required. This study aims to compare the performance of asphaltic mixture that was constructed by using two different additives, which are Wetbond-SP and Retona Blend and by two different natural aggregates. There were three tests conducted for each sample variation in this study, namely Marshall, Cantabro Loss, and Indirect Tensile Strength (ITS) tests. From the test results, it was found that adding the Retona Blend 55 to the asphaltic mixture resulted in better Marshall, Cantabro Loss, and ITS test results compared to the asphaltic mixture that was mixed with Wetbond-SP.